Mechanical Thrombectomy for M1 Subocclusive Thrombus With Lateral Lenticulostriate Artery Occlusion: A Case Report and Literature Review - Yajima, Hirohisa; Koizumi, Satoshi; Miyawaki, Satoru; Saito, Nobuhito (Frontiers in Neurology, 2022)
The treatment for middle cerebral artery subocclusive thrombi is not standardized. Here, we report a case of M1 subocclusive thrombus with lateral lenticulostriate artery occlusion that was successfully treated with mechanical thrombectomy. This article describes a treatment strategy for M1 subocclusive thrombus, focusing on the indications for mechanical thrombectomy. A 58-year-old male on admission for pneumonia had a sudden onset of dysarthria and motor deficits. He has a history of dilated cardiomyopathy and underwent left ventricular assist device implantation 3 years ago. At onset, his National Institutes of Health Stroke Scale (NIHSS) score was nine. Computed tomography angiography demonstrated a filling defect in the distal right M1 segment of the middle cerebral artery. Angiography confirmed the presence of a subocclusive thrombus within the distal right M1 segment, although peripheral blood flow was maintained. Mechanical thrombectomy was performed for the M1 subocclusive thrombus using a direct aspiration first-pass technique, resulting in successful aspiration of the thrombus on the first pass. After the procedure, recanalization of the lateral lenticulostriate artery was detected, and the patient demonstrated full recovery (NIHSS score 0). Mechanical thrombectomy can be considered as a treatment option in cases of acute ischemic stroke caused by M1 subocclusive thrombus with lateral lenticulostriate artery occlusion, which presents with a high NIHSS score or neurological deterioration.